The Impact of Trade with Border Effect on GDP per Capita: Global Evidence - Hansen Tandra; I Gusti Ayu Putu Mahendri; Sujianto Sujianto; Bahtiar Rifai; Zamroni Salim; Helena da Silva; Yulia Pujiharti (Economies)
Many countries worldwide share borders that offer several benefits, such as easier access, faster knowledge transfer, and more efficient trade diplomacy. However, reliance on land-border trade alone has not been consistently shown to increase GDP per capita or vice versa. This study investigates the relationship between trade and GDP per capita by distinguishing trade between land-border countries and non-land-border countries. The analysis applied two-stage least squares (2SLS) estimation using data from 87 countries with land borders covering 2010 to 2021. The share of trade to land and non-land borders around the world was dominated by China, Germany, and the United States, with a share of more than 10%. The results revealed a negative relationship between trade with land-border countries and GDP per capita, while trade with non-land-border countries showed a positive effect. To enhance the benefits of land-border trade, improving governance and infrastructure are essential to sustain its impacts in the future.